Advancing a performance management tool for service delivery in local government - Ilse M. Schoeman; James Chakwizira (Administrative Sciences, 2023)
Various strategic plans compiled by the local levels of government seek to advance the need to integrate strategic planning frameworks and improve service delivery and related content through the application of performance management tools. From the perspective of municipalities, all policies and plans at all levels of government need to be articulated with empirical based plan-level formulation and in compliance with set performance assessment criteria. Using South Africa as a case study, the methodology of the paper included a theoretical analysis of available (but applicable) performance management tools and processes. The focus and outcome were the development of a simplified performance management tool that supports elementary prioritization of projects and the setting of standards to address the growing needs, service backlogs, and informality challenges, thereby enhancing sustainable planning and development applicable to developing countries. The study findings highlight, firstly, the prevalence of persistent service delivery gaps in local government. Secondly, local government performance management and strategic plan implementation is constrained by measurement data, standards, and information gaps. Thirdly, inadequate legislative frameworks and strategic instruments applicable to local government in developing countries adds another layer of performance management gap dimensions. Fourthly, there is misalignment between policies, legislative provisions, and local needs in terms of a set of applicable measurement tools and standards relevant in a developing country. Fifthly, an oversight role gap exists in terms of clearly defining the roles and scope of responsibilities concerning performance management. These above-mentioned shortcomings read together constitute a service delivery performance management tools gap that needs to be overcome if improved service delivery is to be achieved. In view of the above-stated considerations, a simplified performance management tool to enhance service delivery in local government had to be developed. The developed simplified performance management tool assumes that the application of performance management assessment processes is to be aligned throughout all spheres of government.
Keywords: 350; assessment tools; modelling; performance management; project prioritisation; service delivery; strategic plans